2002
DOI: 10.1038/sj.ejhg.5200805
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the appropriate use of genetic tests in infertile couples

Abstract: Research on genetic causes of male and female infertility rapidly expanded in the last years, following the development of in vitro fertilising techniques. Genetic tests are now available to explore the cause of the infertility and assess the risk of a given couple to transmit its genetic characteristics. This allows at-risk couples to take an informed decision when electing for a medically assisted reproduction. It also allows the professionals to offer a prenatal diagnosis when appropriate. Thus, the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
3
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 73 publications
(42 reference statements)
5
110
3
5
Order By: Relevance
“…It could be approximated that the overall incidence of a chromosomal factor in infertile males ranges between 2% to 8%, with a mean value of 5% [3]. This value increases to about 15% in azoospermic males, largely due to cases with 47,XXY aneuploidy.…”
Section: Introductionmentioning
confidence: 99%
“…It could be approximated that the overall incidence of a chromosomal factor in infertile males ranges between 2% to 8%, with a mean value of 5% [3]. This value increases to about 15% in azoospermic males, largely due to cases with 47,XXY aneuploidy.…”
Section: Introductionmentioning
confidence: 99%
“…CF carrier testing in infertile couples (non-CBAVD couples) Recommendation of CF screening in the case of in vitro fertilization (IVF) procedures 62 is not widely shared among European Genetics societies, as the risk of carrying a CF mutation is not significantly higher than that of the general population. However, this issue may be discussed with couples in a genetic counselling session before IVF.…”
Section: Recommendations For Pnd Practicementioning
confidence: 99%
“…This possibility has suggested that all CBAVD individuals and their partners should undergo genetic testing of the most common CFTR mutations before ART. 16,17 However, the utility of screening the couples candidates for an ART procedure for problems not related to obstructive azoospermia in the male partner and without a family history of CF is still debated. 18 In this study we report the results of a multicentric molecular screening of the most common CFTR gene mutations in 1195 couples undergoing ART, due to different causes of infertility.…”
Section: Introductionmentioning
confidence: 99%